Decreased CD73+ Double-Negative T Cells and Elevated Level of Soluble CD73 Correlated With and Predicted Poor Immune Reconstitution in HIV-Infected Patients After Antiretroviral Therapy - Wang, Xinyue; Zhang, Leidan; Du, Juan; Wei, Yuqing; Wang, Di; Song, Chuan; Chen, Danying; Li, Bei; Jiang, Meiqing; Zhang, Mengyuan; Zhao, Hongxin; Kong, Yaxian (Frontiers in Immunology, 2022)
Although extensive use of antiretroviral therapy (ART) has made great progress in controlling HIV replication and improving CD4+ T cell recovery, the immune reconstitution remained insufficient in some patients, who were defined as poor immunological responders (PIRs). These PIRs were at a high risk of AIDS-related and non-AIDS complications, resulting in higher morbidity and mortality rate. Thus, it is a major challenge and urgently needed to distinguish PIRs early and improve their immune function in time. Immune activation is a key factor that leads to impaired immune reconstitution in people living with HIV (PLWH) who are receiving effective ART. Double negative T cells (DNT) were reported to associate with the control of immune activation during HIV infection. However, the precise mechanisms by which DNT cells exerted their suppressive capacity during HIV infection remained puzzled. CD73, both a soluble and a membrane-bound form, display immunosuppressive effects through producing adenosine (ADO). Thus, whether DNT cells expressed CD73 and mediated immune suppression through CD73-ADO pathway needs to be investigated. Here, we found a significant downregulation of CD73 expression on DNT cells in treatment-naïve PLWH (TNs) compared to healthy controls, accompanied with increased concentration of sCD73 in plasma. Both the frequency of CD73+ DNT cells and the level of plasma sCD73 recovered after ART treatment. However, PIRs showed decreased percentage of CD73+ DNT cells compared to immunological responders (IRs). The frequency of CD73+ DNT cells was positively correlated with CD4+ T cell count and CD4/CD8 ratio, and negatively correlated with immune activation in PLWH. The level of sCD73 also showed a negative correlation to CD4+ T cell count and CD4/CD8 ratio. More importantly, in the present cohort, a higher level of sCD73 at the time of initiating ART could predict poor immune reconstitution in PLWH after long-term ART. Our findings highlighted the importance of CD73+ DNT cells and sCD73 in the disease progression and immune reconstitution of PLWH, and provided evidences for sCD73 as a potential biomarker of predicting immune recovery.